RANCANG BANGUN PROTOTYPE SISTEM PROTEKSI MOTOR DC BERBASIS MIKROKONTROLER DENGAN NOTIFIKASI TELEGRAM - Al Baihaqqi, Difa; Paramytha, Nina; Fitriani, Endah; Ariyadi, Tamsir (LPPM Universitas Putera Batam, 2025)
CTP / CTCP machine which is a machine used in the printing industry that functions to make printing plates. CTP (Computer to Plate) CTCP (Computer to Conventional Plate). Continuous usage of this machine may cause the vacuum blower motor to overheat and shut off, which could impede the creation of printing plates and ultimately halt output. The performance of the machine can be enhanced by using protective system technology on the vacuum blower motor. By using microcontroller Node MCU ESP 8266 as control system, using a DS18B20 as temperature sensor, two fan as cooler, PZEM 017t as voltage and current monitoring motor, LCD 16x2 as display showing the values of current, voltage, DC motor temperature, DC motor speed control, and telegram to monitoring system realtime. The research’s output is a prototype that uses a DC motor as vacuum blower motor for monitoring and cooler if the DC motor temperature reaches a certain point, it will automatically notify the user via a chatbot (Telegram). So that when used with the plate printing machine, it can subsequently aid in improving output results.